2022
DOI: 10.1007/s00467-022-05755-3
|View full text |Cite
|
Sign up to set email alerts
|

The complement system in pediatric acute kidney injury

Abstract: The complement cascade is an important part of the innate immune system. In addition to helping the body to eliminate pathogens, however, complement activation also contributes to the pathogenesis of a wide range of kidney diseases. Recent work has revealed that uncontrolled complement activation is the key driver of several rare kidney diseases in children, including atypical hemolytic uremic syndrome and C3 glomerulopathy. In addition, a growing body of literature has implicated complement in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 123 publications
0
4
1
Order By: Relevance
“…However, its excessive activation in the later phases of sepsis could contribute to the development of MOF. It has been reported that the complement system is activated in AKI [4] and that C5b-9 deposition is observed in the tubulointerstitial area of an SA-AKI model [19]. Although the serum levels of C3 and C4 were normal, those of both C5a and C5b-9 were elevated in the patients in this study at the time of CRRT introduction.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…However, its excessive activation in the later phases of sepsis could contribute to the development of MOF. It has been reported that the complement system is activated in AKI [4] and that C5b-9 deposition is observed in the tubulointerstitial area of an SA-AKI model [19]. Although the serum levels of C3 and C4 were normal, those of both C5a and C5b-9 were elevated in the patients in this study at the time of CRRT introduction.…”
Section: Resultscontrasting
confidence: 51%
“…The complicated pathogenesis of AKI is thought to contribute to the poor prognosis of SA-AKI; therefore, it is crucial to understand the pathogenesis of AKI more precisely. In addition to hemodynamic changes, cell apoptosis, cytokines or reactive oxygen species, and the immune system (including both innate as well as adaptive immune responses) have recently attracted much attention as important components of the pathogenesis of AKI [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment analysis showed that these genes were mainly enriched in Complement and Coagulation Cascades, Cell Cycle, and Oxidoreductase Activity. Recent studies have shown that the complement system is activated in pediatric patients with AKI, and complement proteins may serve as biomarkers and therapeutic targets for AKI ( Stenson et al, 2023 ). Our recently study has reported that EGR1 increased SOX9 expression in renal tubular epithelial cells by directly binding to the promoter of the Sox9 gene, thereby promoting proliferation of SOX9 + cells after AKI ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the complement system in AKI, with resultant amplification of the inflammatory response, has received recent attention [23 ▪ ]. A predominant role for C5a in ischemic AKI has been identified during formation of the final membrane attack complex.…”
Section: Alterations In the Inflammatory Responsementioning
confidence: 99%